Vitamin E: Regulatory role in the cardiovascular system - SÖZEN, AHMET ERDİ; KARTAL ÖZER, NESRİN (WILEY, 2019)
Cardiovascular disease (CVD) is one of the major causes of morbidity and mortality, all around the world. Vitamin E is an important nutrient influencing key cellular and molecular mechanisms as well as gene expression regulation centrally involved in the prevention of CVD. Cell culture and animal studies have focused on the identification of vitamin E regulated signaling pathways and involvement on inflammation, lipid homeostasis, and atherosclerotic plaque stability. While some of these vitamin E functions were verified in clinical trials, some of the positive effects were not translated into beneficial outcomes in epidemiological studies. In recent years, the physiological metabolites of vitamin E, including the liver derived (long- and short-chain) metabolites and phosphorylated (-, -tocopheryl phosphate) forms, have also provided novel mechanistic insight into CVD regulation that expands beyond the vitamin E precursor. It is certain that this emerging insight into the molecular and cellular action of vitamin E will help to design further studies, either in animal models or clinical trials, on the reduction of risk for CVDs. This review focuses on vitamin E-mediated preventive cardiovascular effects and discusses novel insights into the biology and mechanism of action of vitamin E metabolites in CVD. (c) 2019 IUBMB Life, 71(4):507-515, 2019
Keywords: vitamin E; -tocopherol; long-chain metabolites; tocopheryl phosphate; cardiovascular disease; SCAVENGER RECEPTOR EXPRESSION; CORONARY-HEART-DISEASE; DIETARY ANTIOXIDANT VITAMINS; ALPHA-TOCOPHERYL PHOSPHATE; LOW-DENSITY-LIPOPROTEIN; LONG-CHAIN METABOLITES; GAMMA-TOCOPHEROL; ATHEROSCLEROSIS PROGRESSION; INHIBITS ATHEROSCLEROSIS; E SUPPLEMENTATION